2017
DOI: 10.1155/2017/6578621
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stimulation of the HT7 Acupuncture Point to Reduce Ethanol Self‐Administration in Rats

Abstract: Background Alcoholism, which is a disabling addiction disorder, is a major public health problem worldwide. The present study was designed to determine whether the application of acupuncture at the Shenmen (HT7) point suppresses voluntary alcohol consumption in addicted rats and whether this suppressive effect is potentiated by the administration of naltrexone. Methods Rats were initially trained to self-administer a sucrose solution by operating a lever. A mechanical acupuncture instrument (MAI) for objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…HT7 stimulation inhibits GABA neuron activity in the ventral tegmental area (VTA) and reduces the self-administration of alcohol [ 20 ]. We previously showed that use of the mechanical acupuncture instrument (MAI) at the HT7 point effectively reduces alcohol consumption in rats [ 21 ] and that its stimulation regulates immobility and 22-kHz ultrasonic vocalizations (USVs) via σ 1 R in the VTA upon acute alcohol exposure [ 22 ]. The stimulation of HT7 reduced alcohol withdrawal-related tremors, anxiety-like behaviors, and alcohol self-administration in alcohol-dependent rats.…”
Section: Introductionmentioning
confidence: 99%
“…HT7 stimulation inhibits GABA neuron activity in the ventral tegmental area (VTA) and reduces the self-administration of alcohol [ 20 ]. We previously showed that use of the mechanical acupuncture instrument (MAI) at the HT7 point effectively reduces alcohol consumption in rats [ 21 ] and that its stimulation regulates immobility and 22-kHz ultrasonic vocalizations (USVs) via σ 1 R in the VTA upon acute alcohol exposure [ 22 ]. The stimulation of HT7 reduced alcohol withdrawal-related tremors, anxiety-like behaviors, and alcohol self-administration in alcohol-dependent rats.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of specific acupoint stimulation and acupoint combination need to be further studied. A recent study has found that electroacupuncture at the Baihui (DU20) acupoint shows neuroprotective effects via inhibiting the apoptosis of nerve cells, decreasing the abnormally level of β -amyloid-42, and increasing BDNF expression in APP/PS1 transgenic mice [ 37 ]; acupunctureat the Sanyinjiao (SP6) has a role in painless childbirth, in the treatment of urinary and reproductive disorders, and as anesthesia during pelvic surgery [ 38 ]; the HT7 (Shenmen) acupuncture point can ameliorate mental disorders, such as depression, anxiety, and drug addiction [ 39 ]. Importantly, another survey has found that acupuncture at the Baihui (DU20) and Sanyinjiao (SP6) had a role in ameliorating ischemic stroke through neuroprotective effects with anti-inflammation and TRPV-1-mediated antioxidant stress function [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that ethanol in rats results in a 25% reduction in PON-1 activity and a 51% reduction in PON-1 gene expression [19]. Although some studies have reported elevated PON-1 and HDL-C at moderate ethanol levels [19], there is no conclusive evidence suggesting alcohol consumption could be controlled through the development of a sense of physiological and psychological demands [20,21]. Additionally, changes in the concentration of anti-inflammatory agents are different from their function [22].…”
Section: Discussionmentioning
confidence: 99%